Coviretinopathy: COVID-19-induced VEGF-dependent retinopathy - Xiaolu Wang; Xu Jing; Ziheng Guo; Siwen Long; Xiaoting Sun; Sofia Appelberg; Gerald M. McInerney; Mikael Adner; Yihai Cao (Proceedings of the National Academy of Sciences, 2026)
COVID-19 has been associated with high prevalences of retinal diseases in humans. However, cellular and molecular mechanisms that underlie the COVID-19-associated retinopathy remains unknown. Here, we deployed a mouse COVID-19 model to investigate the causative link between SARS-CoV-2 infection and retinopathy development. Our data showed that COVID-19-induced pulmonary hypoxia triggered systemic hypoxia and markedly augmented VEGF expression levels in the retina and plasma. High VEGF levels altered vascular structures and functions in the retina, resulting in neovascularization, vascular disorganization, and increased leakiness. We deployed a terminology of coviretinopathy to accurately describe these COVID-19-induced pathological changes in the retina. Consequently, blocking VEGF by a specific neutralizing antibody (VEGF blockade) completely ablated the COVID-19-associated vascular changes in the retina. Together, these findings provide mechanistic insights into the COVID-19-associated retinopathy and propose a therapeutic paradigm for effective treatment of coviretinopathy.